Perancangan Interior Makeup & Beauty Community Center Di Surabaya - Kim, Renata; Sari, Sriti Mayang (Intra, 2019)
The growth of the cosmetics industry in Indonesia nowdays was caused by the increasing lifestyle and public awareness, especially womens, that pays attention to their appearance and beautify themselves. Moreover, social media such as Facebook, Instagram and others are also some factors in this phenomenon. This issue brings up a new type of public figure who has the knowledge and skills in the beauty fields, both formal and self-taught educational backgrounds, known as the beauty vlogger. Surabaya Glam Squad (SbyGlamSquad) is a beauty vlogger community, and one of the beauty activist in Surabaya. Periodically, they often hold make-up or beauty class events and gatherings with fellow make-up lovers to build a sense of family and share the latest tips and information in the beauty industry, even though there is no special space for these activities.